Islamic epistemology and its relations to scientific method in Islamic law of evidence - Mohamed M.F.; Baharudin A.S.; Abd Hamid Abd Murad; Wafa K.A.; Lukman Abdul Mutalib; Mualimin Mochammad Sahid; Wan Abdul Fattah Wan Ismail (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by Scopus